Do Tumor Locations and Stages at Diagnosis Predict the 5-Year Survival Outcome in Patients with Colorectal Cancer? - Niam, Muhammad S.; Nastiti, Novia Ayuning; Dradjat, Respati S.; Rudijanto, Achmad; Sujuti, Hidayat (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Globally, colorectal cancer (CRC) ranks as the third most common cancer. CRC cases are generally discovered at a more advanced stage, so the patients’ life expectancy is low. The prognostic factors that affect the survival outcome in CRC patients are still limited. AIM: This study aimed to identify factors associated with the 5-year overall survival of CRC patients at Dr. Saiful Anwar Regional General Hospital, Malang. MATERIALS AND METHODS: This study used a retrospective cohort design and obtained data from patients diagnosed with CRC at Dr. Saiful Anwar Regional General Hospital Malang between January and December 2015. The 5-year prognosis factors, tumor clinical characteristics, disease progression, and demographic details were analyzed using Kaplan Meier and Cox regression. RESULTS: Kaplan–Meier analysis showed differences in the survival function based on surgery (p = 0.028) and stages (p = 0.002). There were no differences in the survival function based on gender (p = 0.455), age (p = 0.484), tumor location (p = 0.114), carcino embryonic antigen (0.459), histopathology (p = 0.842), tumor recurrence (p = 0.268), chemotherapy response (p = 0.06), and response description (p = 0.086). Based on the Cox proportional hazard regression, the tumor stage was the only variable that affected the risk of mortality (p = 0.014) with an HR value of 3.500 (CI 95%). CONCLUSION: The tumor stage is a significant predictor of survival, suggesting that higher stages may require more attention and more aggressive treatment than lower stages.